The Diagnostic Significance of Combined Screening and Human Papillomavirus 16 and 18 Cycle Threshold Values for CIN2+ Cervical Lesions - Bai X; Liu YK; Jia YJ; Li DJ; Du NY (Dove Medical Press, 2024)
Xue Bai,1 Ya-Kun Liu,1 Ya-Jing Jia,1 Dao-Juan Li,2 Nai-Yi Du1 1Department of Gynecology, The Fourth Hospital of Hebei Medical University, Shijiazhuang, Hebei Province, 050011, People's Republic of China; 2Cancer Institute, The Fourth Hospital of Hebei Medical University, Shijiazhuang, Hebei Province, 050011, People's Republic of ChinaCorrespondence: Nai-Yi Du, Department of Gynecology, The Fourth Hospital of Hebei Medical University, 12 Jiankang Road, Shijiazhuang, Hebei Province, 050011, People's Republic of China, Tel +8618531116751, Email dunaiyiyi@outlook.comBackground: Although both cervical intraepithelial neoplasia (CIN) II and CIN III carry the potential to progress into cervical cancer, to date, an optimal screening method for CIN2+ (CIN II, CIN III, and cervical cancer) cervical lesions is yet to be established.Methods: In this retrospective study, data from 2035 patients treated at the Fourth Hospital of Hebei Medical University between 2019 and 2021 were analyzed. The screening efficacy of three methods-the ThinPrep cytologic test (TCT) alone, the high-risk-human papillomavirus (HR-HPV) test alone, and the combined TCT and HR-HPV screening for CIN2+ lesions-were assessed using cervical histopathology as the reference standard. Additionally, correlations between HPV16 cycle threshold (Ct) values, HPV18 Ct values, and the severity of cervical lesions were analyzed. Receiver operating characteristic (ROC) curves were plotted to evaluate the diagnostic utility of HPV16 Ct values for CIN2+ lesions.Results: Compared with TCT or HR-HPV testing alone, the combined TCT and HR-HPV test had the highest sensitivity of 98.1% (P < 0.0001), the highest negative predictive value of 99.8% (P = 0.0001), and the lowest missed diagnosis rate of 1.9% (P < 0.0001) for screening CIN2+ lesions. Additionally, the combined test yielded the largest area under the ROC curve (AUC) value of 0.9480. There was a significant difference in HPV16 Ct values for various degrees of cervical lesions (P < 0.001), with the Spearman rank correlation test revealing a significant negative correlation (rs = − 0.447, P < 0.001). The optimal HPV16 Ct value for diagnosing CIN2+ lesions was 29.995, with an AUC of 0.797 (P < 0.0001).Conclusion: The combination of TCT and HR-HPV testing was the most effective method for screening CIN2+ lesions. Furthermore, HPV16 Ct values were negatively correlated with the severity of cervical lesions, with a threshold of 29.995 potentially indicating the presence of CIN2+ lesions.Keywords: CIN2+ cervical lesions, cervical cancer, combined test, HPV16 Ct value, HR-HPV, TCT